The genus Macronemus Dejean, 1835 (Insecta: Coleoptera: Cerambycidae: Lamiinae): two new species, new records and a new synonymy - Machado, Vanessa S.; Monné, Marcela L. (Zootaxa, 2013)
The genus Macronemus Dejean, 1835 is redescribed and two new species are described: Macronemus mimus sp. nov. from Brazil (Bahia to Santa Catarina) and Argentina and Macronemus giuglarisi sp. nov. from French Guiana and Brazil (Amapá, Amazonas). M. verrucosus (Pascoe, 1866) is considered a new synonym of M. asperulus White, 1855. New distributional data and a key to the seven species of the genus are provided.